Optimization methods for computer-aided design - Bandler, John W. (Numerical Applications Group, Department of Electrical Engineering, University of Manitoba, 1969)
This paper surveys recent automatic optimization methods which either have found or should find useful application in the optimal design of microwave networks by digital computer.
Report produced by John W. Bandler as a post-doctoral fellow with the Department of Electrical Engineering, University of Manitoba, Winnipeg, Canada. This work is licensed under a Creative Commons Attribution-Non-Commercial-No-Derivatives 4.0 International License.
Keywords: automatic optimization; computer-aided design